A Comparative Study of Teachers’ Career Satisfaction According to Their Demographics at Becora Technical Senior High School in Dili, Timor Leste - Maria Gusmao, Antoninho; Eamoraphan, Suwattana (Scholar: Human Sciences, 2016)
This study was conducted to compare the teachers’ career satisfaction according to their demographics at Becora technical senior high school in Dili, Timor Leste. The objectives of this study were: (1) to identify teachers’ demographics including their gender, age, educational background and years of teaching in Becora Technical Senior High School in Dili, Timor Leste, (2) to identify the level of teachers’ career satisfaction in Becora Technical Senior High School in Dili, Timor Leste, (3) to compare teachers’ career satisfaction at Becora Technical Senior High School in Dili, Timor Leste according to their educational background, and years of teaching. The purposive sampling method based on the location of the school was used in this study. Totally 85 teachers of Becora technical senior high school were used as the participants. The returned questionnaire from the respondents or teachers of the school was analyzed by the frequency and percentage, mean and standard deviation, and independent sample t-test. The findings about the levels of teachers’ career satisfaction from the objective one showed that, there were 71 (83.5 %) of teachers are male while the female respondent were 14 (16.5 %) teachers from the total of 85 teachers at Becora technical senior high school in Dili, Timor Leste. On the other side, there were teachers less than or equal 30 years old are 31 (36.5%) while more than 30 years old are 54 (63.5%) from the total of teachers at Becora technical senior high school. Moreover, teachers were got bachelor degree are 67 (78.8%) while teachers who got the higher than bachelor were 18 (21.2%) from the total of the teachers. Overall teachers’ career satisfaction at Becora technical senior high school was high meaning that, teachers were satisfy with their career as teachers with their professional growth opportunity, responsibility, good relationship, and satisfaction with salary. There were no significant difference between years of teaching and their educational background. The study concluded with recommendation for practice and for future.